Navigating Emerging Adulthood: The Role of Religious Coping in Promoting Flourishing Among Indonesian University Students - Qonita, Aisyah; Saleh, Airin Yustikarini (Utan Kayu Publishing, 2025)
This study examined the relationship between positive and negative religious coping and flourishing, conceptualized through the PERMA model of subjective well-being, among Indonesian university students in emerging adulthood. Emerging adulthood (ages 18–25) is a developmental stage marked by identity exploration and emotional transitions, making religious coping a potential protective factor for psychological flourishing. A total of 278 participants completed online questionnaires assessing religious coping and well-being. Data were analyzed using Spearman’s rho and partial correlation controlling for age, gender, and education. Results showed a significant positive association between positive religious coping and well-being (ρ = .284, p .001, 95% CI [0.16, 0.39]) and a weak negative association for negative religious coping (ρ = –.101, p = .033, 95% CI [–0.22, 0.02]). Effect sizes were small (R² = .08 and R² = .01), and post-hoc power analysis indicated adequate statistical power (1–β = .99). The strongest link was observed in the meaning dimension, underscoring spirituality’s central role in constructing purpose and acceptance. Although the effects were modest, the findings highlight that positive religious coping contributes to flourishing within Indonesia’s collectivist and religious culture, serving as a psychological resource that supports meaning-making and emotional well-being during the transition to adulthood.